DISCOVERY OF A NEW MAYFLY SPECIES (EPHEMEROPTERA, BAETIDAE) NEAR CENDERAWASIH UNIVERSITY CAMPUS IN PAPUA, INDONESIA - Thomas Kaltenbach; Suriani Surbakti; Nikita J. Kluge; Jean-Luc Gattolliat; Michel Sartori; Michael Balke (BRIN Publishing (Penerbit BRIN), 2021)
Material collected just behind the Cenderawasih University campus in Jayapura, Papua Province, Indonesia, revealed a new species of the Labiobaetis claudiae group, which is here described and illustrated based on larvae, subimago, male and female imagos. The total number of Labiobaetis species on the island New Guinea increased to 33, the total number for Indonesia increased to 26, and the total number of Labiobaetis species worldwide is augmented to 147. A key to the larvae of the L. claudiae group is provided. The interspecific K2P distances between species of the L. claudiae group are between 20% and 23%.